Comparative Study between Brain and Optic Lobe of Falcon (Falco Columbarius) and Owl (Bubo Bubo) - Raflaa S.H. Hussain, Amel A. Al-taee (Pakistan Journal of Medical & Health Sciences, 2022)
Background: In Iraq have been collected 10 Falcon (Falco columbarius) and 10 Owl (Bubo bubo ) to obtain their brain (optic lobe) and histological comparative between them. Method: In recent study have been collected specimens and used hematoxylin and eosin stain and used silver stain to compare between them. Result: Our result show weight of brain of falcon was less than owl (4.2± 0.04830 , 4.7± 0. 05164) respectively while weight of optic lobe of falcon was more than owl (1.2±0.05270 , 1.1± 0.05164) respectively. Optic lobe of falcon was consist of six layers with thickness (770.7 ±0.48305 ) while owl was consist of three layers only with (707.7±0.48305). Conclusion: brain weight of falcon is less than owl because of long distance which be fly and weight of optic lobe of falcon is more than owl because it has high vision more than owl.